HUBUNGAN PELATIHAN PROFESIONALISME GURU DENGAN KINERJA GURU (Penelitian pada Guru di Madrasah Tsanawiyah Ar-Rosyidiyah) - Supiana, Supiana; Hidayat, Wahyu; Nurhaliza, Amelia (Jurnal Inovatif Manajemen Pendidikan Islam, 2022)
Teachers are required to improve their performance so that they can become professional teachers. The better the professionalism of the teacher, the better the quality of education. That is why teachers need to be given the opportunity to improve their performance, namely through teacher professionalism training. This tudy aims to describe the reality of teacher professionlism training, teacher performance, and the relationship beetween teacher professionalism training and teacher performance. Thi research is a quantitative research. The population in this study were all teachers of Madrasah Tsanawiyah Ar-Rosyidiyah as many 33 teachers and the sampling was saturated. The data collection techniques used were questionnaires and documentation study. The research instrument test used validity and reliability test, while the data analysis use correlation analysis. The result showed that the teacher professionalism training and teacher performance at Madrasah Tsanawiyah Ar-Rosyidiyah were in the high category. Based on the result of the correlation analysis, it is stated that there is significant relationship between teacher professionalism training an teacher performance at Madrasah Tsanawiyah Ar-Rosyidiyah of 0.785, which means that teh level of the relationship is in the strong category, so that the hypothesis in this study can be accepted. The contribution of teacher professionalism training to teacher performance was 61.5%, this means that 38.5% was influenced by other factors.